Socio-Economic Characteristics and Consumption Patterns of Family Beneficiaries of the Family Hope Program (PKH) and Their Relationship with Family Expenditure: A Case Study in Budiman Village, East Jambi District, Jambi City - Tasya Nurjannah; Hardiani Hardiani; Parmadi Parmadi (International Journal of Economics, Commerce, and Management, 2026)
The Family Hope Program (PKH) is a conditional social assistance program designed to reduce poverty in Indonesia, including in Budiman Village, East Jambi District, Jambi City, which has the largest number of PKH beneficiary families in the city. This study aims to analyze the socio-economic characteristics of the heads of beneficiary households, examine family consumption patterns, and investigate the relationship between the amount of PKH assistance and household expenditure while controlling for income. A quantitative-descriptive approach supported by qualitative data was employed. The study involved 88 respondents selected through proportional random sampling from a population of 113 beneficiary families, complemented by in-depth interviews with beneficiaries and PKH facilitators. Data were analyzed using descriptive statistics, simple linear regression based on the Keynesian consumption function, and partial correlation analysis. The findings indicate that most household heads are women with an average age of 53 years, characterized by low educational attainment and employment in the informal sector. Household income has a positive and significant effect on family expenditure, indicating that consumption increases as income rises, although the tendency to consume declines proportionally at higher income levels, reflecting a subsistence consumption pattern. Furthermore, the relationship between PKH assistance and household expenditure, after controlling for income, is weak and statistically insignificant, suggesting that PKH serves as a complementary source of financial support rather than the primary determinant of household spending. These findings highlight the importance of strengthening the economic empowerment component of PKH to improve the long-term welfare and financial independence of beneficiary families.